KEPEMIMPINAN SHALAHUDDIN AL AYYUBI DALAM PERADABAN ISLAM - Al Ayyubi, Ibnu Imam; Sari, Desi Wulan; Noerzanah, Firda; Nurhasanah, Siti; Setiawan, Siti Sawwa Rahmawati (Jazirah: Jurnal Peradaban dan Kebudayaan, 2024)
Shalahuddin Al Ayyubi is a respected figure in Islamic history and is remembered as one of the most influential figures in the Middle Ages. This research aims to explain more comprehensively the leadership of Shalahuddin Al Ayyubi in Islamic civilization. This research is qualitative descriptive research with a literature study approach that refers to several research data sources and data collection techniques in the form of a study of Islamic civilization from the figure Shalahuddin Al Ayyubi. Data collection was carried out by searching and reconstructing from various sources such as articles in journals, books, and previous research that were relevant to the research study, which were then analyzed in a primordial manner. The focus of the research that will be addressed is the leadership of Shalahuddin Al Ayyubi in Islamic civilization. The data collection technique used in this research is the library research method, namely literature study with the data analysis technique used in this research is the hermeneutic method. In this research, it can be concluded that Shalahuddin Al Ayyubi was a general and Muslim fighter who had an intelligent soul and a noble heart. Shalahuddin Al Ayyubi was a prominent military and political leader, famous for his success in reclaiming the holy city of Jerusalem from the Crusaders. This crusade took place in three periods, namely the first period in 1096 -1144 AD, the second period in 1144 - 1192 AD, and the third period in 1193 -1291 AD. Shalahuddin Al Ayyubi's leadership in Islamic civilization was in sharp contrast to the existence of Ahlusunnah Waljamaah As an Official School, Appointment of Qadhi from the Ahlusunnah Waljamaah Group, Establishment of a Sunni Madrasah, Changing the Orientation of Al-Ahzar University to Sunni, and Elimination of Shiite Books.